Research on the Temperature Distribution of the Hollow Conductors in the Self-circulating Evaporative Inner Cooling System for High Power Rectifier Equipment. Issue 5 (January 2021) - Yan, Jing; Yu, Shunzhou; Cao, Rui
Abstract: In the evaporative inner cooling system for high power rectifier equipment, the thyristor and quick fuse are both cooled double-sided via hollow conductors. Different from the previous study on the system with single structure, the self-circulating system for high power rectifier equipment has composite structure. Then the system with composite structure may show different heat transfer characteristics. So in this paper, the temperature distribution of the horizontal and vertical hollow conductors in the self-circulating system was studied through theoretical analysis and simulation.